Alcohol for Motor Fuel, the "Alko-Tipid" Way - Protacio, A.C. (Philippine Engineering Journal; Vol 2 No 1 (1981), 2021)
The oil crisis of the 70’s created renewed interest in the use of fuel alcohol despite operational and technical problems experienced by many countries the past 70 years. In the Philippines, the crisis motivated experiments which led to the development of alko-tipid. Significant properties of alcohol and gasoline provided design parameters for a simple vapor generating device working on engine vacuum evaporation, permitting the use of low grade alcohol, a renewable fuel, without the need for its dehydration nor any engine modification. Dynamometer and road tests confirmed significant reductions in fuel consumption, increased power and mileage, smoother and cleaner engine performance, and fuel cost savings pf 20-25%. While alko-tipid could be a practical answer to the fuel crisis, the availability of alcohol is a temporary problem.